Protesternas makt i Sverige:: Hur mobilisering och alliansbyggande stoppade vattenkraftverket i Sölvbacka strömmar 1978-79 - Jansson, Jenny; Uba, Katrin (Slagmark - Tidsskrift for idéhistorie, 2015)
This article describes and analyses how small protests against the construction of a hydropower plant at a local level took a national level and led to a rare occasion where Swedish parliament overran a governmental decision. This event in 1979 had significant consequences for the government, which had to pay 270 million kroner in compensation to the enterprise that was willing to build the plant in Sölvbacka in northern Sweden. With reference to the research on political consequences of social movements, we propose that this small group of local activists achieved their goals thanks to the continued protests, help of significant political allies at the local and national level, and the general political context which dominated in Sweden after the elections in 1979. The study demonstrates that even small groups of citizens in remote areas can have an impact on environmental or energy politics by sustaining their mobilisation and gaining support from important political allies.